Patchouli Alcohol Modulates the Pregnancy X Receptor/Toll-like Receptor 4/Nuclear Factor Kappa B Axis to Suppress Osteoclastogenesis - Lu, Qian; Jiang, Chao; Hou, Jialong; Qian, Hao; Chu, Feifan; Zhang, Weiqi; Ye, Mengke; Chen, Ziyi; Liu, Jian; Yao, Hanbing; Zhang, Jianfeng; Xu, Jiake; et al. (Frontiers in Pharmacology, 2021)
Osteoporosis has been on the rise in recent years, and it is primarily characterized by plethoric osteoclast formation and severe bone loss. Millions of people worldwide, especially postmenopausal women, suffer from osteoporosis. The commonly used drugs have many disadvantages. Therefore, it is critical to identify a targeted, safety-ensured drug with fewer toxic side effects. The Chinese medicine monolith patchouli alcohol (PA) exhibits anti-inflammatory effects, and it is used as a treatment for gastroenteritis. However, there is no research on the use of PA in osteoporosis. We found that PA dose-dependently inhibited the receptor activator of nuclear factor kappa-B ligand (RANKL)-induced formation and function of osteoclasts without cytotoxicity. Further, these inhibitions were reflected in the significant effect of patchouli alcohol on the NF-kB signaling pathway, which suppressed transcription factors, like NFATc1 and c‐Fos. We showed that PA activated the expression of the nuclear receptor pregnane X receptor (PXR) and promoted the PXR/Toll-like receptor 4 (TLR4) axis to inhibit the nuclear import of NF-κB (p50 and p65). PA exerted some therapeutic effects on osteoporosis in ovariectomized (OVX) mice, which supports the use of PA as a treatment for osteoporosis in the future.